Is the ideal mother a sensitive mother? beliefs about early childhood parenting in mothers across the globe (2016)
In this article, we test the hypothesis that beliefs about the ideal mother are convergent across cultures and that these beliefs overlap considerably with attachment theory’s notion of the sensitive mother. In a sample including 26 cultural groups from 15 countries around the globe, 751 mothers sorted the Maternal Behavior Q-Set to reflect their ideas about the ideal mother. The results show strong convergence between maternal beliefs about the ideal mother and attachment theory’s description of the sensitive mother across groups. Cultural group membership significantly predicted variations in maternal sensitivity belief scores, but this effect was substantially accounted for by group variations in socio-demographic factors. Mothers living in rural versus urban areas, with a low family income, and with more children, were less likely to describe the ideal mother as highly sensitive. Cultural group membership did remain a significant predictor of variations in maternal sensitivity belief scores above and beyond socio-demographic predictors. The findings are discussed in terms of the universal and culture-specific aspects of the sensitivity construct.